L-shaped multihole-buffering oil-feeding process. (May 2017) - Chen, Liqiong; Fu, Lingdi; Huang, Kun; Lu, Hongfang; Zhang, Zhihao; Wu, Shijuan
An L-shaped multihole-buffering oil-feeding process is proposed, optimized, and experimentally validated to reduce the shock and disturbance to in-tank oil and bottom sediment caused by oil-feeding. Three-dimensional numerical simulation of the flow field inside the oil tank based on the computational fluid dynamics method is conducted using FLUENT software. The influences of design parameters of L-shaped multihole-buffering inlet tubes on the flow field are analyzed, and structures are optimized according to orthogonal testing. The reliability of the numerical simulation results is confirmed by field testing the optimized L-shaped multihole-buffering inlet tubes. Results indicate the following conclusions: (1) after adoption of the L-shaped oil-feeding process, the flow properties of in-tank oil are effectively improved including reduced oil outlet velocity, decreased degree of disturbance between flow points and improved outlet oil quality, as compared to results obtained by traditional I-shaped and J-shaped oil-feeding processes; (2) structural parameter optimization resulted in a decrease of turbulence energy around the outlet tube entrance from 0.004572 to 0.003154 m 2 s −2, while the concentration of oil pumped from the outlet tube increased from 95.19% to 99.23%, demonstrating clear advantages of the proposed optimized scheme; (3) the variation regularity of the water and mechanical impurities contents in the oil pumped from the tanker is in accordance with simulated results, as the liquid height. The accuracy and reliability of the numerical computation method are validated based on the aforementioned observations.